Is structural unemployment a negligible problem? A critical note on the use of mismatch indices - Karl-Heinz Paqué (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1989)
Since the mid-seventies, the general public of some European countries has been listening to a growing chorus of economists and politicians who lament the rising regional imbalances of unemployment. The chorus is especially large in Britain and West Germany where both an approximate north-south divide began to take shape, with the old industrial north and north-west apparently losing ground to the still flourishing south in the common fight against low growth and high unemployment.
Keywords: 330; Theorie der Arbeitslosigkeit; Strukturelle Arbeitslosigkeit; Theorie